Revitalisasi Fungsi Sosial Masjid dalam Pemberdayaan Masyarakat Desa: Studi pada Masjid Al-Mubarokah Desa Bungamas, Kabupaten Lahat - Aulia Nisa Nur Rahma; Desta Nur Khotimah; Citra Anilia; Karmila Sari; Hudaidah Hudaidah; Tyas Fernanda (Indo Publishing, 2026)
This research aims to analyze the revitalization of the mosque's social function in empowering the village community thru a study of Al-Mubarokah Mosque in Bungamas Village, Kikim Timur District, Lahat Regency. The mosque, which has stood since 1915 on waqf land, initially started as a small, simple prayer room, but then underwent gradual development and renovation until it became a two-story permanent mosque capable of accommodating a larger number of worshipers. In addition to serving as a place of worship, the mosque also becomes a center for religious and social activities in the community. This research uses a descriptive qualitative method with data collection techniques thru field observations, interviews with mosque administrators, and documentation. The research results show that Al-Mubarokah Mosque not only serves as a place for performing ritual worship such as congregational prayers but also plays a role in strengthening the religious life and social solidarity of the village community. Various activities such as preaching, study groups, and social programs like sacrificial animal lotteries are able to increase community participation and strengthen the values of togetherness and mutual cooperation. In addition, transparent financial management and a clear organizational structure also support the sustainability of various mosque activities. Thus, the revitalization of the social function of Masjid Al- Mubarokah reinforces its role as an important religious and social institution in supporting the empowerment and development of the Islamic community at the village level.